International training workshop and stakeholder consultations on Enhancing access to quality maize seed and feed in the crop-livestock farming system of Lao PDR - Hpommalath, Siviengkhek; Boualaphanh, Chanthakhone; Tielmann, Tassilo; Issa, Abdurahman Beshir; Mponela, Powell; López Ridaura, Santiago; Krupnik, Timothy Joseph (International Maize and Wheat Improvement Center, 2024)
Objectives: -Understand the challenges and opportunities of the crop-livestock farming nexus and integrate these for a more sustainable and productive system. -Promote synergistic partnerships among value-chain actors in enhancing local access to good quality seed and feed. -Enhance participants’ technical skills in understanding and applying the principles and practices of quality hybrid maize seed production. -Exchange experiences and knowledge from different countries that can be applied to strengthen institutional and human resource capacities across the seed and feed value chains.